PENGARUH CONTENT MARKETING, LIVE STREAMING, DAN ELECTRONIC WORD OF MOUTH (E-WOM) TERHADAP KEPUTUSAN PEMBELIAN PRODUK SKINCARE PADA KONSUMEN E-COMMERCE SHOPEE DI PROVINSI BANTEN - Ratu Syifa Fadilah; Ilham juliandri; Dede Rihan Faradis; Yeni Silvia; Safitri Putri Derajat (Desanta Publisher, 2025)
In the era of globalization, where advancements in digital technology and the growing popularity of e-commerce have significantly influenced consumer behavior, particularly in purchasing skincare products, strategies such as content marketing, live streaming, and electronic word of mouth (E-WOM) have become essential tools for businesses to capture consumer attention. This study aims to evaluate how content marketing, live streaming, and E-WOM affect purchasing decisions for skincare products among e-commerce consumers in Banten Province. The research employs a quantitative approach, utilizing multiple linear regression analysis processed using E-Views 10, with 100 respondents as the sample. The analysis results indicate that, overall, content marketing, live streaming, and E-WOM have a positive and significant influence on purchasing decisions. Thus, all hypotheses proposed in this study are proven to be accepted. These findings suggest that these three variables have a strong impact on purchasing decisions for beauty products through the Shopee e-commerce platform.